2015
DOI: 10.1016/j.mjafi.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography versus hysteroscopy in evaluation of abnormal uterine bleeding

Abstract: Abnormal uterine bleedingTransvaginal sonography Hysteroscopy Endometrial polyp Submucous fibroid a b s t r a c t Background: Abnormal uterine bleeding (AUB) accounts for 33% of female patients referred to gynaecologists. Common causes of AUB include endometrial polyps, endometrial hyperplasia, submucous fibroids and anovulation. Accurate diagnosis of the cause of AUB can reduce the frequency of hysterectomy. This study was aimed at assessing the usefulness of TVS in comparison with hysteroscopy in AUB evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 10 publications
8
33
0
Order By: Relevance
“…These observations were similar to those observed by Goyal, B.K. et al who recommended the use of trans vaginal ultrasound solely prior to initiation of treatment whenever there is no abnormal findings could be detected and to consider hysteroscopy whenever there is no response to medical treatment [14].…”
Section: Discussionsupporting
confidence: 89%
“…These observations were similar to those observed by Goyal, B.K. et al who recommended the use of trans vaginal ultrasound solely prior to initiation of treatment whenever there is no abnormal findings could be detected and to consider hysteroscopy whenever there is no response to medical treatment [14].…”
Section: Discussionsupporting
confidence: 89%
“…6 Goyal et al found that TVUSG had high sensitivity (95%), specificity (94%), PPV (93%), and NPV (96%) in detecting endometrial pathologies. 7 In present study TVUSG's sensitivity, specificity, PPV and NPV for detecting endometrial pathologies were 77%, 32%, 75% and 32%, respectively. Although the sensitivity, PPV and NPV were similar to previous reports, the specificity of TVUSG in detecting endometrial pathologies was lower than those reported in the literature.…”
Section: Discussionsupporting
confidence: 46%
“…Two recent studies also demonstrated the high accuracy of ultrasonography in the diagnosis of endometrial disease among reproductive‐age women . Those studies recommend that transvaginal ultrasonography should be used as the first step in the investigation of uterine bleeding anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,21 Again, this difference could be due to technologic improvements in ultrasonography equipment.Two recent studies also demonstrated the high accuracy of ultrasonography in the diagnosis of endometrial disease among reproductive-age women. 25,26 Those studies recommend that transvaginal ultrasonography should be used as the first step in the investigation of uterine bleeding anomalies. If the uterine cavity shows no anomalies, then further evaluation is not required and treatment of symptoms may be initiated.…”
mentioning
confidence: 99%